PERJANJIAN KERJA DAN PERLINDUNGAN HAK KARYAWAN PERSPEKTIF HUKUM KETENAGAKERJAAN - Maulana, Puja; Fatriani, Fenny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The employment agreement is the legal basis that regulates the relationship between employers and employees in the world of employment. In this context, protecting employee rights is crucial to ensuring welfare and justice in the workplace. This article aims to analyze employment agreements from a labor law perspective, with a focus on the aspect of protecting employee rights. Through a normative approach, this research explores various regulations governing employment agreements, including employment law and company regulations. In addition, this article discusses the challenges faced in implementing the protection of employee rights, such as unfairness in employment agreements and lack of law enforcement. The research results show the importance of collaborative efforts between governments, employers and labor unions to create a fair and sustainable work environment. The conclusions of this study emphasize the need for more comprehensive labor policy reform to protect employee rights and strengthen harmonious industrial relations.